Waktu Kerja Fleksibel Dan Supervisi Dalam Meningkatkan Kinerja Karyawan Studi: Sales Eksekutif Pt. Theta Nusantara Jaya Daerah Cianjur Dan Sukabumi - Hasan Wirayuda; Asep Muhamad Ramdan; Resa Nurmala (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine whether the application of flexible working time and supervision has an influence and can improve the performance of executive sales employees at PT. Theta Nusantara Jaya Cianjur and Sukabumi areas. The research method used is a quantitative method. The sample in this study were 42 respondents who are sales executives of PT. Theta Nusantara Jaya Cianjur and Sukabumi areas using saturated sampling technique. Data were obtained through a research questionnairewhich was distributed to all samples containing 24 servers regarding the variables of flexible working time, supervision and employee performance, using a differential semantic measurement system. Furthermore, the data that has been obtained will be analyzed with various tests to answer the hypothesis in this study. The results showed that there is a positive and sinificant influence between monitoring variables on employee performance and simultaneously the application of flexible working time and supervision can improve the performance of executive sales employees at PT. Theta Nusantara Jaya Cianjur and Sukabumi areas.